Using Games to Enhance Skill and Fitness. (3rd March 2020) - Reed, Jacob P.
Abstract : As practitioners it is imperative to understand that these challenges among youth participants are occurring and to do what we can inside of practice and competition to facilitate the fun and joy that sport is typically associated. How can coaches keep practice goals focused on improving performance along with integrating activities or practice sets that target young athletes' desire for novelty, fun, and enjoyment? A common approach that can help coaches develop this practice structure is the integration of small-sided games.